Review of "English-Lahu lexicon" - Butler, Katie L. (2024)
Following nearly 20 years after the publication of James Matisoff’s Dictionary of Lahu (1988), the corresponding reversed English-Lahu Lexicon is a welcome addition to Lolo-Burmese resources as well as a testament to the advancement in methods of lexicography. With more than 5,400 head entries and 10,000 sub entries, the 514-page English-Lahu Lexicon (hereafter referred to as ELL) is designed for quick reference to the English headword and corresponding Lahu gloss. Matisoff describes ELL as the “bare bones” (p. xxii) of its 1,436-page dictionary predecessor, which provides detailed etymologies, cross-references, and usage examples of the Lahu entries. ELL is published by the University of California Press and is a subproject of the Sino-Tibetan Etymological Dictionary and Thesaurus project (STEDT) at U.C. Berkeley